A Polylogarithmic Bound in the Nonlinear Roth Theorem. (13th October 2020) - Peluse, Sarah; Prendiville, Sean
Abstract: We show that sets of integers lacking the configuration $x$, $x+y$, $x+y^2$ have at most polylogarithmic density.